P557 Sustained remission in inflammatory bowel disease patients after discontinuing infliximab; the ongoing reluctance to stop biologics. (25th January 2019) - Ryan, T; Coffey, L; Mullen, A; Leyden, J; MacMathuna, P
Abstract: Background: Biologic therapy, including infliximab is the current gold standard treatment of both Crohn's disease (CD) and ulcerative colitis (UC). Long-term treatment is associated with adverse effects and significant healthcare budget burden. Previous studies into the discontinuation of biologic treatment for patients in clinical remission have shown 40–49% relapse rates by 24 month follow-up. The aim of this study was to critically evaluate the clinical/biomarker/financial outcome of biologic discontinuation in IBD patients from 2006 to 2018. Methods: A single-centre retrospective analysis of all patients discontinuing infliximab treatment due to disease remission defined by clinical, endoscopic and biomarkers (C-reactive Protein or Faecal Calprotectin) response. The mean length of infliximab received before discontinuation was 38.5 months. Data were gathered on patients' biomarkers, endoscopy scores and clinical status at baseline, 3, 6, 12, and 24 months. Combination drug therapies and changes in medications were documented and a cost analysis performed. Results: The study identified 30 patients discontinuing infliximab due to disease sustained remission. Data on 22/30 patients were available at 24 months, 91% (20/22) remained in clinical remission. Of the original cohort, 13.3% (4/30) patients had relapsed, resulting in restarting biologic treatment. Of the relapse patients, 75% had CD, 25% UC. After discontinuation 50% ( n = 2) took no other medications for IBD. Cost analysis showed €379351.56 per annum saving from discontinuation of infliximab. Conclusions: This study showed low relapse rates compared with other studies. Demographics were similar in relapse patients vs. the sustained remission cohort. Discontinuation of infliximab for patients in remission was safe and offered substantial savings to the healthcare budget.